THE IMPORTANCE OF DIGITAL MARKETING FOR MICRO AND SMALL BUSINESSES IN THE AFTERMATH OF THE PANDEMIC (CIPEEX, 2025)
This study explores the application of relationship marketing in Brazilian micro and small businesses, particularly in the context of the Covid-19 pandemic, which compelled these companies to seek new strategies to overcome market challenges. Relationship marketing is highlighted as a vital tool for building strong customer relationships, adding strategic value to management processes, and facilitating business decisions. The study's primary objective is to examine how relationship marketing can be employed by micro and small businesses, emphasizing the importance of attracting, winning over, and retaining customers. A total of 26 articles and books from sources such as Google Scholar and Scielo were analyzed.  Findings suggest that companies employing relationship marketing achieve superior market positioning, development, and growth, even amid economic challenges. Micro and small businesses, as defined by the General Law on Micro and Small Companies, encounter unique difficulties due to their size and limited resources. Micro-enterprises are those with annual revenues of up to R$ 360,000.00, while small businesses have revenues between R$ 360,000.00 and R$ 4,800,000.00. These companies play a crucial role in the Brazilian economy, significantly contributing to GDP and local development. The methodology involved a literature review, drawing from academic databases and books on marketing, micro and small businesses, and the Brazilian market. Relationship marketing is identified as an effective response to market shifts, enabling companies to build lasting customer relationships, foster loyalty, and secure a competitive advantage. Marketing strategies encompass actions from customer acquisition to after-sales service, aiming to provide a comprehensive and satisfactory experience. During the pandemic, many businesses faced operational and financial difficulties, making relationship marketing a key tool for overcoming barriers and engaging customers. The adoption of strategies such as digital marketing allowed companies to adapt to the new normal, promoting their products and services more effectively and directly. Digital platforms became essential for enhancing communication with customers and understanding their needs.  Customer relationship management is fundamental to the success of these companies. Relationship marketing aids in creating strategies that add value to products and services, promote customer satisfaction, and encourage repeat purchases. Digital tools, such as social media and e-commerce platforms, have broadened the reach of micro and small businesses, enabling them to compete with larger firms. In conclusion, relationship marketing is a crucial strategy for Brazilian micro and small businesses. It not only aids in attracting and retaining customers but also enhances financial performance and strengthens brand image. Proper application of this tool enables companies to navigate market challenges, especially during crises, and achieve sustainable long-term growth.
Keywords: relationship marketing; micro-enterprises; small businesses; loyalty; customers